A mutação constitucional no contexto brasileiro: um estudo entre a atualização do sentido da norma e a segurança jurídica no constitucionalismo contemporâneo - Venturini, Délcia Teresinha (2022)
This Dissertation is part of the research line "Constitutional Jurisdiction and Democracy" in the concentration area "New Paradigms of Law" of the Master's degree in Law from the University of Passo Fundo - UPF. The goal investigation is to study whether the constitutional mutation, carried out by the Supreme Federal Court, through judicial interpretation, in jurisdiction mechanisms constitutional, brings legal uncertainty to social relations by assigning new meaning to the text of the standard. The theme was limited to the Brazilian context, based on the Federal Constitution of 1988, adopting as a theoretical framework, some theories of normative interpretation. In developing the research, we first sought address the main philosophical ideas of Contemporary Constitutionalism, comparing them with the Democratic Rule of Law and the phenomenon of Judicialization of Law. Some general notions about the theory of legal argumentation; the constructivist hermeneutics of Law for integrity; from thephilosophy of language; legal pragmatism; and the phenomena of self-containment and judicial activism. In the second chapter, issues related to the need for harmonization of democracy, constitutional jurisdiction and implementation of the legal norm. Contemporary Constitutionalism seeks reconcile the preservation of the fundamental values ​​of democracy, with the evolution history of the very understanding of these values. The post-positivist perspective influences the formation of a more modern constitutional interpretation contemporary. Some points of the creation process of the legal norm and its implementation. In the third chapter, the phenomenon of constitutional mutation, through judicial interpretation, and its relationship with the principle of legal security in social relations. The normative activity of judges must observe argumentative criteria, justify their legal reasoning and the new meaning attributed to the constitutional text. You must also observe the modulation of its mutative decisions, in prestige to the protection of trust.